Marat y la escalada a los extremos - Barahona Plaza, Ángel Jorge (2019)
The cult of Reason and the Supreme Being, in Marat's mind, became the program of continuous de-Christianization. Everyone who refused to leave the Christian creed had the guillotine secured.